Tagging and mapping of prominent structural genes on chromosome arm 7DL of common wheat - Groenewald, Johannes Zacharias (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD (Agric)) -- Stellenbosch University, 2001.